Fracture toughness Kic of austempered ductile iron - Šiđanin, Leposava; Gerić, Katarina; Bajić, Vladimir; Kakaš, Damir (Journal of Production Engineering, 1990)
Austempered Ductile Iron is considered a new class of metallic material, offering competitiveness and serving as an alternative to forged components. Over the last five years, this material has seen extensive use. The Institute for Production Engineering, part of the Yugoslav Committee of Technical Sciences, has embarked on a project to investigate Austempered Ductile Iron. This is in response to the ongoing need for a deeper understanding of this novel material and the necessity to establish parameters for its successful application in mechanical engineering. In this paper, we focus on determining both conventional mechanical properties and fracture toughness (KIC) for as-cast nodular iron grade NI40 with a ferritic matrix microstructure and austempered ductile iron with low bainite and retained austenite. The heat treatment required to achieve the austempered bainitic matrix microstructure was conducted at 300°C. Single-edge notched specimens were prepared for each type of iron and were precracked through fatigue prior to conducting fracture toughness testing. The testing and analytical procedures adhered to the relevant ASTM and British Standards. The results indicate that the samples with the bainitic matrix met the KIC criteria, whereas the results for the ferritic samples did not. The austempered bainitic iron exhibited high yield and tensile strength, satisfactory Charpy impact properties, and promising fracture toughness values, making it a viable material for use in industrial construction components.